High-resolution Imaging of a TESS Control Sample: Verifying a Deficit of Close-in Stellar Companions to Exoplanet Host Stars - Colin Littlefield; Steve B. Howell; David R. Ciardi; Kathryn V. Lester; Mark E. Everett; Elise Furlan; Rachel A. Matson; Sergio B. Fajardo-Acosta; Crystal L. Gnilka (The Astronomical Journal, 2024)
The large number of exoplanets discovered with the Transiting Exoplanet Survey Satellite (TESS) means that any observational biases from TESS could influence the derived stellar multiplicity statistics of exoplanet host stars. To investigate this problem, we obtained speckle interferometry of 207 control stars whose properties in the TESS Input Catalog (TIC) closely match those of an exoplanetary host star in the TESS Object of Interest (TOI) catalog, with the objective of measuring the fraction of these stars that have companions within ∼1.″2. Our main result is the identification of a bias in the creation of the control sample that prevents the selection of binaries with 0.″1 ≲ ρ ≲ 1.″2 and Δmag ≲3. This bias is the result of large astrometric residuals that cause binaries with these parameters to fail the quality checks used to create the TIC, which in turn causes them to have incomplete stellar parameters (and uncertainties) in the TIC. Any stellar multiplicity study that relies exclusively upon TIC stellar parameters to identify its targets will struggle to select unresolved binaries in this parameter space. Left uncorrected, this selection bias disproportionately excludes high-mass-ratio binaries, causing the mass-ratio distribution of the companions to deviate significantly from the uniform distribution expected of FGK-type field binaries. After accounting for this bias, the companion rate of the FGK control stars is consistent with the canonical 46% ± 2% rate from Raghavan et al., and the mass-ratio distribution agrees with that of binary TOI host stars. There is marginal evidence that the control-star companions have smaller projected orbital separations than TOI host stars from previous studies.